The Routledge handbook of religion and nationalism - Haynes, Jeffrey, 1953- (Routledge international handbooks, 2026)
The Routledge Handbook of Religion and Nationalism comprehensively surveys the sub-disciplinary area of religious nationalism, an interaction between religion and nationalism.The handbook has a global focus, including sections on how, why and with what effects religion and nationalism impact politically both domestically and internationally, as well as discussing the future of the field and religious nationalism 'on the ground'. Bringing together a range of expert contributors, the handbook is split into two main parts: core issues and country case studies. Religions studied include Islam, Christianity, Hinduism, Judaism and Buddhism, across countries in Asia, Europe, the Middle East and North Africa, Sub-Saharan Africa, North America and South America. The core issues examined cover nationhood as a concept; historical perspectives on nationalism; theoretical approaches to nationalism; the state; populism; violence and conflict; immigration; terrorism; globalisation; the post-secular world; and foreign policy.Given the comprehensive nature of the handbook, it provides crucial, complementary reading for students, scholars and professionals across politics, religion and policy making.